Perlis story map: an inspiring insights of Perlis / Kamilia Kamaruzzaman - Kamaruzzaman, Kamilia (2023)
Perlis aspires to strengthen and enhance the government's delivery system and digital experience to improve people's quality of life and catalyse Perlis' economic development towards Perlis as a City State in 2030 aligned with the Perlis Digital Plan 2021-2025 and Perlis State Tourism Physical Planning Master Plan. However, the lack of a centralized platform integrating data on Perlis' tourist attractions affects information accessibility. Thus, this study aims to promote Perlis tourism through “Story Map: An Inspiring Insights of Perlis” in order to further the region’s promotion by empowering Perlis’s attempts towards Perlis Go Digital. The objectives of this study are i) to design a tourism storyboard using a variety of integrated crowdsourcing techniques and ii) to build an interactive tourism-storytelling-project for Perlis. This study was carried out by designing a storyboard to produce a story map. The information and location of the tourist attractions were acquired through various crowdsourcing platform such as Google Earth, social media, websites, and others. Subsequently, these information were integrated into one platform to centralize the data pertaining to Perlis’ tourist attractions. The prototype has been developed and published which consists of tourists’ attractions displayed based on their categories, which are natural, heritage, and purpose-built attractions. Network analysis was carried out to find the best route for user who might use this product itinerary section in the Story Map. Finally, the user-acceptance test has been carried out to ensure that the application meets the end-user's requirements and functions impeccably in real-world situations. To conclude, Story Maps are one of the significant applications to be used to ensure that an interesting Story Maps can be developed to boost the promotion of the Perlis’ area.